Fluorinated Derivatives of Digalloyl-Flavan-3-ol Induce Autophagic Cell Death by Forming Granular Aggregates Containing Mitochondria - Ryo Doge; Yuki Nishino; Akiko Saito (MDPI AG, 2023)
Flavan-3-ol derivatives are polyphenolic compounds with multifunctional properties. One of the flavan-3-ol derivatives, green tea catechin epigallocatechin gallate, is known to have anticancer activity as one of its multifunctional properties. We have studied the synthesis of flavan-3-ol derivatives and conducted structure-activity relationship studies; we found that the fluorinated derivatives exhibited high toxicity against HeLa and A549 cells. It was confirmed that the cytotoxicity was affected by the conformation of the flavan-3-ol skeleton and that the 2,3-cis form was dominant. The addition of fluorinated compounds increased the amount of intracellular mitochondrial superoxide, abolished the membrane potential of mitochondria, and, interestingly, formed granular aggregates containing mitochondria. When the level of LC3-II, a marker of autophagy induction, was confirmed, it suggested that the addition of the fluorinated compounds promoted autophagy. These results suggest that the novel highly cytotoxic fluorinated flavan-3-ol compound synthesized in this study promotes autophagy and induces cell death by triggering mitochondrial dysfunction. We believe that these results suggest the possibility of conferring more functionality through structural transformations of flavan-3-ol derivatives.